Analyzing Customer Loyalty Through Satisfaction in PT Garuda Indonesia - Dito Putra Hardanto; Prasetyo Hadi; Maria Assumpta Wikantari (Ilomata International Journal of Social Science, 2026)
The COVID-19 pandemic has significantly disrupted the global aviation industry, including the operational and financial performance of Garuda Indonesia as Indonesia’s national airline. In the post-pandemic recovery period, maintaining service performance and retaining passengers has become an important managerial concern. This study examines the relationship between service quality, customer satisfaction, and customer loyalty among passengers of Garuda Indonesia. A quantitative survey design was employed using purposive sampling of 200 respondents who had previously used Garuda Indonesia’s services, with the sample predominantly drawn from Surabaya and its surrounding areas. Data were collected through an online questionnaire distributed to passengers within this geographic scope. The analytical technique applied was Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess the relationships among the constructs. The empirical results indicate that perceived service quality is positively associated with customer loyalty. However, customer satisfaction was not found to significantly mediate the relationship between service quality and loyalty in the examined sample. These findings suggest that improvements in service performance may directly relate to loyalty perceptions among surveyed passengers, although the mediating role of satisfaction appears limited within the context of this study. Given the cross-sectional survey design, purposive sampling approach, and the geographic concentration of respondents in Surabaya and nearby regions, the results should be interpreted as reflecting patterns within this specific sample rather than representing all Garuda Indonesia customers. Nevertheless, the study offers empirical insights that may assist airline management in prioritizing service quality strategies during the post-pandemic recovery phase.